Agonist-Antagonist Coactivation Enhances Corticomotor Excitability of Ankle Muscles. (3rd September 2019) - Kesar, Trisha M.; Tan, Andrew; Eicholtz, Steven; Baker, Kayilan; Xu, Jiang; Anderson, Joanna T.; Wolf, Steven L.; Borich, Michael R.
Abstract : Spinal pathways underlying reciprocal flexion-extension contractions have been well characterized, but the extent to which cortically evoked motor-evoked potentials (MEPs) are influenced by antagonist muscle activation remains unclear. A majority of studies using transcranial magnetic stimulation- (TMS-) evoked MEPs to evaluate the excitability of the corticospinal pathway focus on upper extremity muscles. Due to functional and neural control differences between lower and upper limb muscles, there is a need to evaluate methodological factors influencing TMS-evoked MEPs specifically in lower limb musculature. If and to what extent the activation of the nontargeted muscles, such as antagonists, affects TMS-evoked MEPs is poorly understood, and such gaps in our knowledge may limit the rigor and reproducibility of TMS studies. Here, we evaluated the effect of the activation state of the antagonist muscle on TMS-evoked MEPs obtained from the target (agonist) ankle muscle for both tibialis anterior (TA) and soleus muscles. Fourteen able-bodied participants (11 females, age:26.1 ± 4.1 years) completed one experimental session; data from 12 individuals were included in the analysis. TMS was delivered during 4 conditions: rest, TA activated, soleus activated, and TA and soleus coactivation. Three pairwise comparisons were made for MEP amplitude and coefficient of variability (CV): rest versus coactivation, rest versus antagonist activation, and agonist activation versus coactivation. We demonstrated that agonist-antagonist coactivation enhanced MEP amplitude and reduced MEP CVs for both TA and soleus muscles. Our results provide methodological considerations for future TMS studies and pave the way for future exploration of coactivation-dependent modulation of corticomotor excitability in pathological cohorts such as stroke or spinal cord injury.